On drinking - Bukowski, Charles (Ecco, an imprint of HarperCollinsPublishers, 2019)
"The definitive collection of works on a subject that inspired and haunted Charles Bukowski for his entire life: alcohol. Charles Bukowski turns to the bottle in this revelatory collection of poetry and prose that includes some of the writer's best and most lasting work. A self-proclaimed "dirty old man," Bukowski used alcohol as muse and as fuel, a conflicted relationship responsible for some of his darkest moments as well as some of his most joyful and inspired. In On Drinking, Bukowski expert Abel Debritto has collected the writer's most profound, funny, and memorable work on his ups and downs with the hard stuff--a topic that allowed Bukowski to explore some of life's most pressing questions. Through drink, Bukowski is able to be alone, to be with people, to be a poet, a lover, and a friend--though often at great cost. As Bukowski writes in a poem simply titled "Drinking," "for me/it was or/is/a manner of/dying/with boots on/and gun/smoking and a/symphony music background." On Drinking is a powerful testament to the pleasures and miseries of a life in drink, and a window into the soul of one of our most beloved and enduring writers."--Jacket flap